Composite identities, hybrid writing: Brazil, Quebec and the Antilles - Bernd, Zilá (Literatura e Sociedade, 2006)
The article shows that the reading of the francophone literatures of the Americas (Quebec and the Caribbean), comparing them to the Brazilian literature, from the perspective of hybridization, favors the perception of the non-essentialist nature of the identity construction of many contemporary writers of the Americas. It also leads us to the conclusion that most of the fictionists of the Americas take from different sources and claim several affiliations, which are all valued with no hierarchy whatsoever. In what regards the literatures of the three Americas, the authors adopt strategies to provide the reader with the active role of choosing among a variety of possible interpretations, creating an interstitial space, a third margin of reading and interpretation.